Rent Taxes and Royalties in Designing Fiscal Regimes for Non-Renewable Resources - Robin Boadway; Michael Keen (Center for Economic Studies and ifo Institute (CESifo), 2014)
A fundamental issues in designing any fiscal regime for non-renewable resources is the balance between rent taxes and royalties. This paper reviews the core issues that arise, in terms of both efficient rent extraction and correcting various market failures. Issues of asymmetric information, for instance, can rationalize using both instruments. The paper also shows that, even though they effectively involve the choice of distinct parameters at several dates, rent taxes are not subject to the time consistency problem that is central to the extractive industries, but royalties are (although time consistent royalty policy is efficient conditional on initial resource stocks).
Keywords: H21; H25; Q30; 330; rent tax; royalties; resource taxation